Supporting Police Integrity in the Philadelphia (Pennsylvania) Police Department, 1991-1998 and 2000 - Greene, Jack R. ([Verlag nicht ermittelbar], 2004)
This study investigated police integrity in the Philadelphia Police Department (PPD). Its primary goal was to identify risk factors for negative police behaviors and outcomes using information readily available to the department. Part 1, Academy and Background Data, contains background information and academy records data for 1,949 PPD officers from 17 academy classes for the years 1991 to 1998. Part 2, Survey Data, contains data collected in 2000 on the attitudes of a sample of 499 PPD officers. Variables in Part 1 cover background information, including history of misconduct and disciplinary actions. Variables in Part 2 include measurements of officer cynicism and attitudes toward ethical issues.